Preparation of TiO2 nanoparticles by Sol-Gel route - Y. Bessekhouad; D. Robert; J. V. Weber (International Journal of Photoenergy)
Nanosized titanium oxide (TiO2) powders were prepared by emulsification-gelation technology, hydrolysis and reflux process. Starting precursor (Tetraisopropylorthotitanate Ti(OC3H7)4) was modified by 1,4 cyclohexane diol (C6H14O2), hydrogen peroxide (H2O2) and Triethanol amine (C6H15NO3). Titanium tetrachloride was also used as precursor. The effect of methanol on ethanol solvent was also investigated. The powders were analyzed by X-ray diffraction (XRD) and BET technique. Scanning electron microscopy observation was used for agglomerate observations. The photoactivity of the products obtained was taken as efficiency of Benzamide photodegradations.